Urine biochemistry assessment in the sequential evaluation of renal function: Time to think outside the box - Maciel, Alexandre T.; Vitorio, Daniel; Osawa, Eduardo A. (Frontiers in Medicine, 2022)
Urine biochemistry (UB) remains a controversial tool in acute kidney injury (AKI) monitoring, being considered to be of limited value both in terms of AKI diagnosis and prognosis. However, many criticisms can be made to the studies that have established the so called “pre-renal paradigm” (used for decades as the essential physiological basis for UB assessment in AKI) as well as to more recent studies suggesting that UB has no utility in daily clinical practice. The aim of this article is to describe our hypothesis on how to interpret simple and widely recognized urine biochemical parameters from a novel perspective, propose the rationale for their sequential assessment and demonstrate their usefulness in AKI monitoring, especially in the critical care setting.